GIS-Based Approach Of Mapping Water Pollutant Concentration Of Sg. Galing, Kuantan - Mohamad Syazwan, Mohd Latif (2023)
Water pollution results from harmful substances built into its composition, making the water toxic and unusable for humans and animals. This degradation in water also causes negative effects on the environment. There are many things we do that have an impact on the greatness of water in our environment. The irresponsible thinking of the network to throw garbage into the river has caused the river to be polluted with garbage. For example, open dumping and deforestation can cause rivers to be polluted. And, arguably, we all make a contribution to this problem by calling for paper and wood made from the bush. any other example is sewage waste water. Sewage dumped into the river can pose a serious health hazard to people who bathe or swim in it. Water pollution has killed thousands and cost billions, yet we had absolutely no idea it would happen to us lucky citizens. What we should acknowledge is that pollutants damage the environment we depend on. So our way to overcome this problem is to reduce the use of plastic, reuse and recycle. This way can curb the problem of sediment pollution caused by the dumping of rubbish into the river.